The intersection of social justice activism and college athletics - Davis, Connor Nikole (Kansas State University, 2021)
College student athletes have been participating in a movement to raise public awareness about the injustices and inequities experienced by marginalized communities. Student athletes can reach large audiences with their platforms yet are only allowed to use this platform within certain parameters. Athletic departments and higher education institutions hold a special relationship with the student athletes that allows them to monitor and restrict student athletes’ public statements and actions. Meanwhile, the majority of student athletes speaking out on social issues such as racial injustice is black and indigenous people of color (BIPOC). The opportunity for student athletes, especially BIPOC, to civically engage is important for the future of a more equal society and the student athletes’ holistic development. Therefore, I investigate how athletic departments can support marginalized student athletes in their social justice activism. I analyze literature from two areas of study, organizational communication and holistic student development, to provide recommendations to collegiate athletic departments on how they can better support their marginalized student athletes in their social justice activism. Organizations like athletic departments that operate in a system that recognizes power, utilizes emotion, and views their members as whole human beings with commitments outside of their organization membership can create a more positive, supportive environment. Holistic student development is a tool to facilitate this system through its mission to develop the whole person within and outside of a field of study. Holistic student development takes shape in the form of student organizations, clubs, resources, etc. Athletic departments, higher education, and overall society can benefit from this organization approach to learn to build community through difference.
Keywords: Social justice; Holistic student development; College athletes; Diversity; Activism; BLM; Critical race theory; Organizational communication